Lithium ion battery diaphragm, preparation method thereof and lithium ion battery
By designing the organic coating with gaps and island structures with gaps on lithium -ion battery septum, it solves the problem of tightly adhesion coating in existing technologies to hinder the infiltration of electrolyte infiltration, realize the improvement of battery fast charging performance and Enhancement of adhesion.
Patent Information
- Application Number
- CN202411943711.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The bonding coating of the existing lithium-ion battery separator becomes dense after rolling, hindering the penetration of the electrolyte into the bonding point structure and resulting in a loss of charge and discharge rate.
Design a lithium -ion battery diaphragm, which contains the ring -shaped structure and/or island structure with the gap part. The gap forms a breakpoint, allowing the electrolyte to transmit the inside and outside of the bonding point. The coating material includes a polymer that is evenly applied by coating or other coating methods on the porous substrate.
By forming a breakpoint point structure, the free transmission of the electrolyte is achieved, which significantly improves the fast charging performance of the battery, and enhances the adhesion between the diaphragm and the positive and negative electrode.
Smart Images

Figure CN119381704A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery separators, and in particular to a lithium ion battery separator and a preparation method thereof, and a lithium ion battery. Background Art
[0002] In order to improve the performance of lithium-ion battery separators, researchers have developed coating materials represented by metal oxides to improve the heat resistance of separators, and have also developed adhesive coatings with adhesive polymers as the main material to improve the adhesion between separators or heat-resistant coatings and positive and negative electrodes. Among them, adhesive coatings are mostly achieved by spraying.
[0003] In order to improve the charge and discharge rate of lithium ions in the battery, the bonding coating adopts a dispersed arrangement method, which is different from the full coverage coating method of the heat-resistant coating. While playing its bonding role, the dispersed bonding points have a certain thickness, playing the role of a partition, to facilitate the penetration of the electrolyte between the diaphragm or heat-resistant coating and the electrode.
[0004] The existing spraying process can make the bonding material particles form a regular or randomly dispersed ring or dot structure on the surface of the membrane. However, these ring or dot structures become dense after the rolling process, which hinders the penetration of electrolyte into the bonding point structure, thereby hindering the transmission of lithium ions in the bonding point after injection, resulting in a loss of charge and discharge rate.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The first object of the present invention is to provide a lithium-ion battery separator, the organic coating of which includes a ring structure and / or an island structure with a notch, the notch forms a breakpoint, and can realize the transmission of electrolyte inside and outside the bonding point, thereby greatly improving the battery fast charging performance. The problem that the bonding coating of the prior art becomes dense after rolling, thereby hindering the electrolyte from penetrating into the bonding point structure is solved.
[0007] The second object of the present invention is to provide a method for preparing a lithium-ion battery separator, which has the advantages of being simple and easy to operate, having a short process, and being suitable for mass production.
[0008] A third object of the present invention is to provide a lithium ion battery having a fast charge and discharge rate.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: The present invention first provides a lithium-ion battery separator, comprising a porous substrate and an organic coating arranged on at least one surface of the porous substrate, wherein the material of the organic coating comprises a polymer, and the organic coating comprises a plurality of dot structures, wherein the dot structures comprise a ring structure having at least one notch and / or an island structure having at least one notch; the maximum value of the height of the dot structure is X, and the height of the notch is ≤0.5X.
[0010] Furthermore, the annular structure has at least two notches.
[0011] Furthermore, the island structure has at least two notches.
[0012] Furthermore, the height of the dot-like structure is 1 μm to 30 μm.
[0013] Furthermore, the shape of the outer contour of the orthographic projection of the dot-shaped structure on the porous substrate includes at least one of a circle, an ellipse and a quasi-circle.
[0014] Furthermore, the diameter of the circumscribed circle of the dot-like structure is 100 μm to 2000 μm.
[0015] Furthermore, the projection areas of each of the dot-like structures and the notch portions thereof on the porous substrate are SD and SQ respectively, then 0.01 <SQ / SD<0.8。
[0016] Furthermore, a plurality of the dot-shaped structures are arranged at intervals.
[0017] Furthermore, the area coverage of the organic coating on the porous substrate is 1% to 30%.
[0018] Furthermore, the loading amount of the organic coating is 0.05 g / m 2 ~4g / m 2 .
[0019] Furthermore, the loading amount of the organic coating is 0.2 g / m 2 ~2g / m 2 .
[0020] Furthermore, the porous substrate includes at least one of PE, PP, non-woven fabric, PET, PVDF, PU, PA, PI, organic-inorganic blended film, and PP / PE / PP composite film.
[0021] Further, the polymer includes at least one of polyvinylidene chloride, polyvinylidene fluoride, vinylidene fluoride and hexafluoropropylene copolymer, polytetrafluoroethylene, polyacrylate, polymethacrylate, polyoxyethylene, polyvinyl acetate, polyoxypropylene, polystyrene, styrene-butadiene copolymer, polyacrylonitrile, acrylonitrile-butadiene copolymer, acryl rubber, butyl rubber, fluororubber, polyepichlorohydrin, polyphosphazene, polyvinylpyridine and styrene-butadiene rubber.
[0022] Furthermore, the particle size D50 of the polymer is 0.1 μm to 10 μm.
[0023] The present invention further provides a method for preparing the lithium ion battery separator, comprising the following steps: coating a slurry containing a polymer on at least one surface of a porous substrate, and then drying.
[0024] The present invention also provides a lithium ion battery, comprising the lithium ion battery separator.
[0025] Compared with the prior art, the present invention has the following beneficial effects: The organic coating in the lithium-ion battery separator provided by the present invention includes a ring structure with a notch and / or an island structure with a notch, and the notch forms a breakpoint, which enables the transmission of the electrolyte inside and outside the bonding point, thereby greatly improving the fast charging performance of the battery. In addition, the polymer can improve the bonding force between the separator and the positive and negative electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 A schematic diagram of the structure of the lithium-ion battery separator provided by the present invention; Figure 2 A schematic cross-sectional view of the ring structure provided by the present invention; Figure 3 A cross-sectional schematic diagram of an island structure provided by the present invention; Figure 4 A schematic diagram of a ring structure with different numbers of notches provided by the present invention, wherein: Figure 4 (a) is a schematic diagram of a ring structure with a gap. Figure 4 (b) is a schematic diagram of a ring structure with two notches. Figure 4 (c) is a schematic diagram of a ring structure with three notches. Figure 4 (d) is a schematic diagram of a ring structure with four notches. Figure 4 (e) is a schematic diagram of a ring structure with six notches. Figure 4 Middle (f) is a schematic diagram of a ring structure with twelve notches; Figure 5 A schematic diagram of the structure of the island structure provided by the present invention; Figure 6 Another schematic diagram of the structure of the island structure provided by the present invention; Figure 7 A schematic structural diagram of the ring structure provided by the present invention.
[0028] Reference numerals: 10-porous substrate; 20-point structure; 21-ring structure; 22-island structure; 23-notch. DETAILED DESCRIPTION
[0029] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0030] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0031] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0032] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0033] In a first aspect, the present invention provides a lithium ion battery separator, such as Figure 1 The structure schematic diagram of the lithium ion battery separator provided by the present invention is shown in a top view, which includes a porous substrate 10 and an organic coating disposed on at least one surface of the porous substrate 10, wherein the material of the organic coating includes a polymer, and the organic coating includes a plurality of dot structures 20, see Figure 1 As shown, the dot-shaped structure 20 includes a ring-shaped structure 21 having at least one notch 23 and / or an island-shaped structure 22 having at least one notch 23. Figure 2 FIG. 2 is a cross-sectional schematic diagram of a ring structure 21 having a notch portion 23 provided by the present invention. Figure 3 FIG. 2 is a schematic cross-sectional view of an island structure 22 having a notch portion 23 provided by the present invention.
[0034] It can be understood that the dot-shaped structure 20 is a protrusion with a certain height, see Figure 5 , Figure 6 and Figure 7 shown.
[0035] It can be understood that the annular structure 21 refers to an annular structure with a hollow center, see Figure 7 The island structure 22 has a protrusion on the outside, and the height of the protrusion on the outside is greater than the height at the center. The heights of the various parts at the center can be the same or different. Figure 5 or Figure 6 shown.
[0036] It can be understood that the number of the dot-shaped structures 20 is multiple, that is, at least two, for example, three, five, eight, ten, twenty, thirty, fifty, seventy, one hundred or more.
[0037] The maximum height of the dot-shaped structure 20 is X, the height of the notch 23 is Y, and Y≤0.5X.
[0038] It is understandable that the dot-like structure 20 may be uneven, with protrusions of different heights. In other words, the height of the dot-like structure 20 is not a fixed value, but is within a certain range. Among them, the maximum height value of the dot-like structure 20 is X, or the distance between the highest point of the dot-like structure 20 and the porous substrate 10 is X. The height of the notch 23 (or the distance between the notch 23 and the porous substrate 10) is less than or equal to 0.5 times X. For example, the height of the notch 23 may be 0.49 times, 0.48 times, 0.45 times, 0.4 times, 0.35 times, 0.3 times, 0.25 times, 0.2 times, 0.15 times, 0.1 times, 0.05 times of X; the height of the notch 23 may also be 0.
[0039] The organic coating in the lithium-ion battery separator provided by the present invention includes a ring structure 21 having a notch 23 and / or an island structure 22 having a notch 23. The notch 23 forms a breakpoint, which realizes the transmission of electrolyte inside and outside the bonding point, thereby greatly improving the fast charging performance of the battery.
[0040] In addition, the separator contains a polymer, which can improve the adhesion between the separator and the positive and negative electrodes.
[0041] In some specific embodiments, in order to further improve the fast charging performance of the battery, the annular structure 21 has at least two notch portions 23; wherein the notch portions 23 can be set to three, four, five, six, eight, ten, twelve, sixteen, twenty or more, for example.
[0042] like Figure 4 The structure diagram of the ring structure 21 with different numbers of notches 23 is shown. Figure 4 (a) is a schematic structural diagram of a ring structure 21 having a notch 23. Figure 4 (b) is a schematic structural diagram of a ring structure 21 having two notches 23. Figure 4 (c) is a schematic structural diagram of a ring structure 21 having three notches 23. Figure 4 (d) is a schematic structural diagram of a ring structure 21 having four notches 23. Figure 4 (e) is a schematic structural diagram of a ring structure 21 having six notches 23. Figure 4 (f) is a schematic structural diagram of the ring structure 21 having twelve notches 23 .
[0043] In some specific implementations, in order to further improve the fast charging performance of the battery, the island structure 22 has at least two notch portions 23; wherein the notch portions 23 can be, for example, set to three, four, five, six, eight, ten or more.
[0044] In some specific embodiments, in order to further improve the fast charging performance of the battery, the height of the dot-like structure 20 is 1 μm to 30 μm, including but not limited to 1 μm, 2 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 23 μm, 25 μm, 27 μm, 30 μm, or any point value or range value between any two of them. It is understandable that the height range does not include the height of the notch 23. Among them, when the protrusion of the dot-like structure 20 is flat, the height of the dot-like structure 20 is a fixed value. When the dot-like structure 20 is uneven, the height of the dot-like structure 20 is a range value.
[0045] In some specific embodiments, the shape of the outer contour of the orthographic projection of the dot structure 20 on the porous substrate 10 includes at least one of a circle, an ellipse, and a quasi-circle.
[0046] To further improve the fast charging performance of the battery, the diameter of the circumscribed circle of the dot structure 20 is 100 μm to 2000 μm; including but not limited to the point value of any one of 100 μm, 200 μm, 300 μm, 500 μm, 800 μm, 1000 μm, 1200 μm, 1500 μm, 1700 μm, 2000 μm or the range value between any two of them.
[0047] In some specific embodiments, the projected areas of each dot structure 20 and its notch portion 23 on the porous substrate 10 are SD and SQ respectively, and SD and SQ satisfy: 0.01 < SQ / SD < 0.8. The value of SQ / SD includes but not limited to the point value of any one of 0.015, 0.02, 0.025, 0.03, 0.05, 0.08, 0.1, 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.75, 0.78 or the range value between any two of them. Controlling this ratio can obtain a higher charge and discharge rate.
[0048] In some specific embodiments, a plurality of the dot structures 20 are arranged at intervals, or in a dispersed arrangement. While the polymer plays its bonding role, the dispersed bonding points have a certain thickness and can play the role of a separator to facilitate the penetration of the electrolyte between the separator or the heat-resistant coating and the electrode sheet.
[0049] In some specific embodiments, the area coverage rate of the organic coating on the porous substrate 10 is 1% to 30%; including but not limited to the point value of any one of 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 23%, 25%, 28%, 30% or the range value between any two of them. When the coverage rate of the organic coating is within this range, the adhesion between the separator and the electrode sheet and the air permeability of the separator can be guaranteed.
[0050] In some specific embodiments, the loading amount (referring to the single-sided loading amount) of the organic coating is 0.05 g / m 2 ~4 g / m 2 ; including but not limited to 0.05 g / m 2 、0.07 g / m 2 、0.1 g / m 2 、0.15 g / m 2 、0.2 g / m 2 、0.23 g / m 2 、0.25 g / m 2 、0.28 g / m2 , 0.3g / m 2 , 0.33g / m 2 , 0.35g / m 2 , 0.37g / m 2 , 0.4g / m 2 , 0.5g / m 2 , 0.6g / m 2 , 0.8g / m 2 , 1g / m 2 , 1.2g / m 2 , 1.5g / m 2 , 1.6g / m 2 , 1.8g / m 2 , 2g / m 2 , 3g / m 2 3.5g / m 2 , 4g / m 2 Any point value in or any range value between the two. It can be understood that the load refers to the weight of the organic coating per unit area. The load of the organic coating in this range can ensure the adhesion between the diaphragm and the electrode.
[0051] In some specific embodiments, the loading amount of the organic coating (referring to the loading amount on a single surface) is 0.2 g / m 2 ~2g / m 2 The loading amount of the organic coating in this range can further improve the adhesion between the diaphragm and the electrode.
[0052] In some specific embodiments, the porous substrate 10 includes at least one of PE, PP, non-woven fabric, PET, PVDF, PU, PA, PI, an organic-inorganic blended film, and a PP / PE / PP composite film.
[0053] In some specific embodiments, a heat-resistant coating is further included between the porous substrate 10 and the organic coating. The heat-resistant coating can improve the heat resistance of the diaphragm. The heat-resistant coating contains any metal oxide commonly used in the art, and the present invention is not limited thereto.
[0054] In some specific embodiments, the polymer includes at least one of polyvinylidene chloride, polyvinylidene fluoride, vinylidene fluoride and hexafluoropropylene copolymer, polytetrafluoroethylene, polyacrylate, polymethacrylate, polyoxyethylene, polyvinyl acetate, polyoxypropylene, polystyrene, styrene-butadiene copolymer, polyacrylonitrile, acrylonitrile-butadiene copolymer, acryl rubber, butyl rubber, fluororubber, polyepichlorohydrin, polyphosphazene, polyvinylpyridine and styrene-butadiene rubber.
[0055] In some specific implementations, the organic coating further includes a binder, and the binder may be any binder material commonly used in the art, and the present invention is not limited thereto.
[0056] In some specific embodiments, the organic coating further includes a dispersant, and the dispersant may be any material commonly used in the art, such as sodium dodecyl sulfate, but is not limited thereto.
[0057] In some specific embodiments, the particle size D50 of the polymer is 0.1 μm to 10 μm, including but not limited to 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.9 μm, 0.9 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, or any range between two of them. Controlling the particle size of the polymer is beneficial to its uniform distribution on the separator, thereby improving the adhesion between the separator and the positive and negative electrodes.
[0058] In a second aspect, the present invention provides a method for preparing the lithium-ion battery separator, comprising the following steps: coating a slurry containing a polymer on at least one surface of a porous substrate 10, and then drying.
[0059] The method has the advantages of simple operation, easy implementation, short process and suitability for mass production.
[0060] In some specific embodiments, the coating method includes any coating method commonly used in the art, such as at least one of roller coating, contact printing and spray coating, but is not limited thereto.
[0061] As an example, when roller coating is performed, implementation methods including but not limited to gravure and transfer can be used, and a ring-shaped / island-shaped pattern containing breakpoints can be engraved on the gravure / transfer roller to carry small droplets, and the pattern can be scattered or continuous to form a ring-shaped / island-shaped pattern structure containing breakpoints.
[0062] When contact printing is performed, a printing method including but not limited to silk screen printing, ink printing, etc. can be used to engrave a ring-shaped / island-shaped pattern including breakpoints on the printing template.
[0063] When spraying, a point spraying method can be used. Point spraying technology includes but is not limited to thermal, piezoelectric, electrofluidic, and ultrasonic technologies, etc. The nozzle is engraved with a ring / island pattern containing breakpoints.
[0064] In some specific embodiments, the method for preparing the slurry containing the polymer includes: uniformly mixing the polymer, the binder and water.
[0065] In a third aspect, the present invention provides a lithium ion battery, comprising the lithium ion battery separator.
[0066] The lithium-ion battery has a fast charge and discharge rate.
[0067] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0068] Example 1 The method for preparing the lithium ion battery separator provided in this embodiment comprises the following steps: (1) 14 parts by weight of vinylidene fluoride and hexafluoropropylene copolymer particles, 0.7 parts by weight of polyacrylonitrile binder and 85.3 parts by weight of deionized water were mixed and stirred at room temperature to form a uniform slurry to obtain a polymer slurry. The vinylidene fluoride and hexafluoropropylene copolymer particles are secondary particles formed by agglomeration of primary particles, wherein the particle size D50 of the primary particles is 0.2 μm, and the particle size D50 of the secondary particles is 5.8 μm.
[0069] (2) Gravure coating: A micro-gravure roller containing multiple circular holes is prepared, the outer diameter of the holes is 350 μm, and there are two gaps of 40 μm width at the edge of the circular holes. The micro-gravure roller and the porous substrate 10 move in the same direction at the same speed, and the polymer slurry obtained in step (1) is transferred to a PE diaphragm (porous substrate 10) with a thickness of 7 μm. The coated diaphragm is dried in an oven at a drying temperature of 60°C to obtain a lithium-ion battery diaphragm.
[0070] The lithium-ion battery separator prepared in this embodiment includes a porous substrate 10 (PE) and an organic coating disposed on one surface of the porous substrate 10. The polymer in the organic coating is a copolymer of vinylidene fluoride and hexafluoropropylene. The organic coating includes a plurality of spaced dot structures 20, and the dot structure 20 includes a ring structure 21 having two notches 23; the maximum height of the ring structure 21 is 10 μm, the height of the notch 23 is 1 to 5 μm (the height varies, so it is a range value), and the height range of the ring structure 21 is 2 to 10 μm (the height varies, so it is a range value). The shape of the circumscribed circle of the positive projection of the ring structure 21 on the porous substrate 10 is circular, and the diameter of the circumscribed circle is 350 μm (there is a certain error, which is an average value). The projected areas of each ring structure 21 and its notch 23 on the porous substrate 10 are SD and SQ, respectively, where the ratio of SQ to SD is SQ / SD=0.04 (there is a certain error, which is an average value). The area coverage of the organic coating on the porous substrate 10 is 5%. The loading of organic coating is 0.5g / m 2 .
[0071] Example 2 The method for preparing the lithium ion battery separator provided in this embodiment comprises the following steps: (1) 18 parts by weight of polymethyl methacrylate polymer particles, 1 part by weight of polyacrylate binder, and 81 parts by weight of deionized water were mixed and stirred at room temperature for 30 minutes to form a uniform slurry. A polymer slurry was obtained. The particle size D50 of the polymethyl methacrylate polymer particles was 4.8 μm.
[0072] (2) Screen printing: A screen with circular mesh holes of 500 μm in diameter was prepared, and three notches of 65 μm in width were formed at the edges of the circular holes. The polymer slurry was transferred through the mesh holes to a 7 μm thick PE diaphragm (porous substrate 10) by a scraper. The screen and the porous substrate 10 moved in the same direction at the same speed. The coated diaphragm was dried in an oven at 80°C to obtain a lithium-ion battery diaphragm.
[0073] The lithium-ion battery separator prepared in this embodiment includes a porous substrate 10 (PE) and an organic coating disposed on one surface of the porous substrate 10, wherein the polymer in the organic coating includes a polymethyl methacrylate polymer, and the organic coating includes a plurality of spaced dot structures 20, wherein the dot structure 20 includes an island structure 22 having three notches 23; the maximum height of the island structure 22 is 12 μm, and the height of the notch 23 is 2 to 6 μm. The height range of the island structure 22 is 4 to 12 μm. The shape of the circumscribed circle of the orthographic projection of the island structure 22 on the porous substrate 10 is circular, and the diameter of the circumscribed circle is 500 μm. The projected areas of each island structure 22 and its notch 23 on the porous substrate 10 are SD and SQ, respectively, wherein the ratio of SQ to SD is SQ / SD=0.06. The area coverage of the organic coating on the porous substrate 10 is 10%. The loading amount of the organic coating is 0.7 g / m 2 .
[0074] Example 3 The method for preparing the lithium ion battery separator provided in this embodiment comprises the following steps: (1) 13.5 parts by weight of vinylidene fluoride and hexafluoropropylene copolymer particles, 0.5 parts by weight of polyacrylonitrile binder, 0.5 parts by weight of sodium dodecyl sulfate and 85.5 parts by weight of deionized water were mixed and stirred at room temperature for 30 minutes to form a uniform slurry to obtain a polymer slurry, wherein the particle size D50 of the vinylidene fluoride and hexafluoropropylene copolymer particles was 230 nm.
[0075] (2) Gravure coating: A micro-gravure roller containing multiple circular holes was prepared, the outer diameter of the holes was 900 μm, and there were four notches with a width of 100 μm at the edge of the circular holes. The micro-gravure roller and the porous substrate 10 moved in the same direction at the same speed, transferring the above polymer slurry to a PE diaphragm (porous substrate 10) with a thickness of 7 μm. The coated diaphragm was dried in an oven at a drying temperature of 50°C.
[0076] The lithium-ion battery separator prepared in this embodiment includes a porous substrate 10 (PE) and an organic coating disposed on one surface of the porous substrate 10. The polymer in the organic coating is a copolymer of vinylidene fluoride and hexafluoropropylene. The organic coating includes a plurality of spaced dot structures 20, and the dot structure 20 includes a ring structure 21 having four notches 23; the maximum height of the ring structure 21 is 26 μm, and the height of the notch 23 is 5 to 13 μm. The height range of the ring structure 21 is 10 to 26 μm. The shape of the circumscribed circle of the positive projection of the ring structure 21 on the porous substrate 10 is circular, and the diameter of the circumscribed circle is 900 μm. The projected areas of each ring structure 21 and its notch 23 on the porous substrate 10 are SD and SQ, respectively, where the ratio of SQ to SD is SQ / SD=0.08. The area coverage of the organic coating on the porous substrate 10 is 16%. The loading amount of the organic coating is 0.9 g / m 2 .
[0077] Example 4 The method for preparing the lithium ion battery separator provided in this embodiment comprises the following steps: (1) 7.5 parts by weight of vinylidene fluoride and hexafluoropropylene copolymer particles, 7.5 parts by weight of polymethacrylate polymer particles, 0.5 parts by weight of polyacrylonitrile binder, 0.5 parts by weight of sodium dodecyl sulfate and 84 parts by weight of deionized water were mixed and stirred at room temperature for 30 minutes to form a uniform slurry to obtain a polymer slurry. The particle size D50 of the vinylidene fluoride and hexafluoropropylene copolymer particles was 230 nm, and the particle size D50 of the polymethacrylate polymer particles was 2.8 μm.
[0078] (2) Gravure coating: A micro-gravure roller containing multiple circular holes was prepared, the outer diameter of the holes was 600 μm, and there were six notches with a width of 100 μm at the edge of the circular holes. The micro-gravure roller and the porous substrate 10 moved in the same direction at the same speed, transferring the above polymer slurry to a PE diaphragm (porous substrate 10) with a thickness of 7 μm. The coated diaphragm was dried in an oven at a drying temperature of 70°C.
[0079] The lithium-ion battery separator prepared in this embodiment includes a porous substrate 10 (PE) and an organic coating disposed on one surface of the porous substrate 10. The polymer in the organic coating includes a copolymer of vinylidene fluoride and hexafluoropropylene and a polymethacrylate polymer. The organic coating includes a plurality of spaced dot structures 20, and the dot structure 20 includes a ring structure 21 having six notches 23; the maximum height of the ring structure 21 is 30 μm, and the height of the notch 23 is 6 to 14 μm. The height range of the ring structure 21 is 12 to 30 μm. The shape of the circumscribed circle of the positive projection of the ring structure 21 on the porous substrate 10 is circular, and the diameter of the circumscribed circle is 600 μm. The projected areas of each ring structure 21 and its notch 23 on the porous substrate 10 are SD and SQ, respectively, where the ratio of SQ to SD is SQ / SD=0.21. The area coverage of the organic coating on the porous substrate 10 is 19%. The loading amount of the organic coating is 1.1 g / m 2 .
[0080] Example 5 The lithium ion battery separator and the preparation method thereof provided in this embodiment are substantially the same as those in embodiment 3, except that SQ / SD=0.6.
[0081] Example 6 The lithium ion battery separator and the preparation method thereof provided in this embodiment are substantially the same as those in Embodiment 3, except that the area coverage of the organic coating on the porous substrate 10 is 25%.
[0082] Example 7 The lithium ion battery separator and its preparation method provided in this embodiment are basically the same as those in embodiment 3, except that the loading amount of the organic coating is 2 g / m 2 .
[0083] Example 8 The lithium ion battery separator and the preparation method thereof provided in this embodiment are substantially the same as those in Embodiment 3, except that the PE separator of the porous substrate 10 is replaced by a PP separator.
[0084] Comparative Example 1 The preparation method of the lithium-ion battery separator provided in this comparative example is basically the same as that of Example 3, except that in step (2), the polymer slurry is sprayed onto a PE separator (porous substrate 10) with a thickness of 7 μm using piezoelectric inkjet printing technology.
[0085] The lithium ion battery separator prepared in this comparative example has no notch 23 on the dot-shaped structure 20 (ring-shaped structure 21 ).
[0086] Comparative Example 2 The lithium ion battery separator and its preparation method provided in this comparative example are basically the same as those in Example 3, except that the height of the notch 23 is 13-20 μm (the maximum value X of the height of the dot structure 20 is the same as that in Example 1, that is, the height of the notch 23 is greater than 0.5X).
[0087] Adhesion test: The lithium-ion battery separators and lithium iron phosphate pole pieces prepared in each embodiment and each comparative example were stacked and hot pressed respectively. The hot pressing conditions were: 95° C., 1 MPa, and hot pressing for 5 min. Then, a peeling test was performed. The test results are shown in Table 1.
[0088] Table 1 Peel test results of various diaphragms
[0089] It can be seen from Table 1 that the bonding forces of Example 3, Comparative Example 1 and Comparative Example 2 are substantially the same.
[0090] In particular, Example 1 has a lower bonding force due to the lower area coverage of the organic coating on the porous substrate 10 and the lower loading of the organic coating. Example 5 has a lower bonding force due to the higher SQ / SD, that is, the area of the notch 23 accounts for a larger proportion.
[0091] Air permeability test: The lithium-ion battery separators and silicone release films prepared in each embodiment and each comparative example were heat-pressed and laminated, and then heat-pressed at 95°C and 1MPa for 5 minutes. Then, the silicone release film was peeled off, and the membrane air permeability test was performed. The results are shown in Table 2. Among them, the air permeability value before lamination refers to the air permeability value of each separator prepared in each embodiment and each comparative example before hot-pressing lamination; the air permeability value after hot-pressing lamination refers to the air permeability value of each separator after the silicone release film is peeled off after hot-pressing lamination. The air permeability value is characterized by the Gurley value, which refers to the time required for a specific amount of air to pass through a membrane of a specific area at a specific pressure (standard Gruley: the time for 100mL of gas to pass through a 1 square inch membrane at a pressure of 4.88 inches of water column).
[0092] Table 2 Air permeability test results of each diaphragm
[0093] It can be seen from Table 2 that the air permeability of the diaphragms in each embodiment increases less after hot pressing, while the air permeability of Comparative Example 1 and Comparative Example 2 increases more after hot pressing. This shows that the diaphragms in each embodiment do not have serious pore blockage after hot pressing, which is conducive to the transmission of electrolyte inside and outside the bonding point, thereby improving the fast charging performance of the battery.
[0094] In summary, the diaphragm provided by the present invention has excellent comprehensive performance.
[0095] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A lithium ion battery separator, characterized in that: It includes a porous substrate and an organic coating arranged on at least one surface of the porous substrate, the material of the organic coating includes a polymer, the organic coating includes a plurality of dot-like structures, the dot-like structures include a ring-like structure with at least one notch and / or an island-like structure with at least one notch; the maximum value of the height of the dot-like structure is X, and the height of the notch is ≤0.5X.
2. The lithium-ion battery separator according to claim 1, characterized in that: At least one of the following conditions is met: (1) The annular structure has at least two notches; (2) The island structure has at least two notches.
3. The lithium-ion battery separator according to claim 1, characterized in that: The height of the dot structure is 1 μm to 30 μm.
4. The lithium-ion battery separator according to claim 1, characterized in that: At least one of the following conditions is met: (1) The shape of the outer contour of the orthographic projection of the dot-like structure on the porous substrate includes at least one of a circle, an ellipse and a quasi-circle; (2) The diameter of the circumscribed circle of the dot-like structure is 100 μm to 2000 μm; (3) The projected areas of each of the dot-like structures and the notch on the porous substrate are SD and SQ respectively, then 0.01 <SQ / SD<0.8。 5. The lithium-ion battery separator according to claim 1, characterized in that: The plurality of dot-shaped structures are arranged at intervals.
6. The lithium-ion battery separator according to claim 1, characterized in that: At least one of the following conditions is met: (1) The area coverage of the organic coating on the porous substrate is 1% to 30%; (2) The loading amount of the organic coating is 0.05 g / m 2 ~4g / m 2 ; (3) The loading amount of the organic coating is 0.2 g / m 2 ~2g / m 2 .
7. The lithium-ion battery separator according to claim 1, characterized in that: The porous substrate includes at least one of PE, PP, non-woven fabric, PET, PVDF, PU, PA, PI, organic-inorganic blended film, and PP / PE / PP composite film.
8. The lithium-ion battery separator according to claim 1, characterized in that: At least one of the following conditions is met: (1) The polymer includes at least one of polyvinylidene chloride, polyvinylidene fluoride, vinylidene fluoride and hexafluoropropylene copolymer, polytetrafluoroethylene, polyacrylate, polymethacrylate, polyoxyethylene, polyvinyl acetate, polyoxypropylene, polystyrene, styrene-butadiene copolymer, polyacrylonitrile, acrylonitrile-butadiene copolymer, acryl rubber, butyl rubber, fluororubber, polyepichlorohydrin, polyphosphazene, polyvinylpyridine and styrene-butadiene rubber; (2) The particle size D50 of the polymer is 0.1 μm to 10 μm.
9. The method for preparing a lithium ion battery separator according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: coating a slurry containing a polymer on at least one surface of a porous substrate, and then drying the slurry.
10. A lithium ion battery, characterized in that: Comprising the lithium ion battery separator as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Separator for secondary battery, manufacturing method therefor, and lithium secondary battery comprising same
CN113841290A
Battery diaphragm, preparation method thereof and battery
CN114665218A
High-cyclicity liquid storage battery diaphragm
CN219303890U
Separator for electrochemical element and electrochemical element using same
WO2020050377A1
Cited By
Diaphragm and gravure coating roller and dispensing roller for manufacturing diaphragm
CN121355537A
Battery diaphragm, preparation method thereof and battery comprising battery diaphragm
CN121484382A
Separator, battery, energy storage device, and electric equipment comprising the same
WO2026194622A1